Dermal nerve status in Hansens disease-histopathological and immunohistochemical study using S-100 - Dr. Noushad Aryadan; Dr. Jyothi CR; Dr Ps Jayalakshmy; Dr. Joy Augustine (International Journal of Pharma and Bio Sciences, 2020)
Destruction of cutaneous nerves is one of the important features of Hansen’s Disease(HD). Identification of remnants of nerve inside the granulomas is difficult with Hematoxylin and Eosin (H&E) stained sections alone. Special staining techniques for nerve identification helps to improve the diagnostic accuracy.S-100 being an immunohistochemical marker for Schwann cells will help in better delineation of nerve fragments. In this study we aim to demonstrate nerve changes in the spectrum of leprosy using S-100 immunostaining. The study was conducted at the department of Pathology at Government Medical College, Thrissur, over a period of one and half years. A total of 51 cases of histologically proven skin biopsies of Hansen’s disease were studied. Routine H&E stain was used for the histopathological diagnosis. S-100 immunoperoxidase stain used to demonstrate the nerve changes. Out of 51 cases, 32 were borderline tuberculoid type, 5 each were borderline lepromatous and indeterminate types, 7 were lepromatous leprosy and 2 were borderline tuberculoid with type I reaction. Nerve twigs were seen in 20 cases on H&E stain and in 32 cases on S-100 staining. Four patterns of nerve involvement were observed in S-100 immunostaining, ie, intact, fragmented, infiltrated and absent. Fragmented pattern was the most common type. To conclude, Hansen's Disease is still a major health problem in India. Dermal nerve involvement is seen in the entire histopathological spectrum of the disease. Our study reaffirms the utility of S-100 staining in demonstrating the destroyed nerves, definite identification of the infiltrate within the nerves and its superiority over H&E for the same.